The Effects of Structured Outdoor Learning on Students’ Attitudes in Environmental Science - Katrina Ann Bautista – Espinola (Future Science / FSH-PH Publications, 2026)
This study examined students’ learning attitudes before and after the integration of structured outdoor activities into Environmental Science instruction. A quasi-experimental research design was used to assess changes across seven dimensions of attitudes toward outdoor learning: Environmental Interaction, Integration, Student Cohesiveness, Teacher Supportiveness, Open-Endedness, Preparation and Organization, and Material Environment. Mean scores increased across all categories after the intervention, with several dimensions shifting from Neutral to Agree. A paired-samples t test revealed a significant difference between students’ pretest and posttest attitude scores toward outdoor learning. The computed t value of −7.65 at the 0.05 significance level supports the effectiveness of integrating structured outdoor learning. Notable improvements were observed in student cohesiveness and open-endedness, indicating enhanced collaboration, engagement, and learner autonomy. Expert evaluation also rated the developed outdoor activities highly in terms of objectives, content alignment, clarity, and cognitive rigor. Overall, the findings provide empirical support for structured outdoor learning as an effective pedagogical strategy in Environmental Science education.